2020
DOI: 10.3389/fchem.2020.00151
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Oxidation of Benzyl Alcohol to Benzaldehyde by Nitrates

Abstract: In this paper, ferric nitrate was used to oxidize benzyl alcohol in a mild condition and demonstrated its better performance compared to HNO 3. In the reaction, the conversion rate and product selectivity could be both as high as 95% in N 2 atmosphere, while the benzaldehyde yield also reached 85% in air. Similar to Fe(NO 3) 3 •9H 2 O, the other metallic nitrates such as Al(NO 3) 3 •9H 2 O and Cu(NO 3) 2 •3H 2 O could also oxidize the benzyl alcohol with high activity. The applicability of Fe(NO 3) 3 •9H 2 O f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Finally, new additional bands were located at 551 and 711 nm with low energy for Fe (LDBu) 2 and Fe (LSO 3 Na) 2 , respectively, which corresponded to the electron transition between d orbitals (d → d transition), as reported for other Fe‐chelates elsewhere. [ 23,24 ] The high observed shift of the d → d transition band between Fe (LDBu) 2 and Fe (LSO 3 Na) 2 , despite the same molecular core, could be due to the difference in the polarity and the electron‐donating or electron‐withdrawing power of the substituted groups in the both coordinated ligands. HLDBu, with nonpolar nature, has high electron‐donating two tert ‐butyl groups, whereas HLSO 3 Na, with polar nature, has high electron‐withdrawing sodium sulfonate group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, new additional bands were located at 551 and 711 nm with low energy for Fe (LDBu) 2 and Fe (LSO 3 Na) 2 , respectively, which corresponded to the electron transition between d orbitals (d → d transition), as reported for other Fe‐chelates elsewhere. [ 23,24 ] The high observed shift of the d → d transition band between Fe (LDBu) 2 and Fe (LSO 3 Na) 2 , despite the same molecular core, could be due to the difference in the polarity and the electron‐donating or electron‐withdrawing power of the substituted groups in the both coordinated ligands. HLDBu, with nonpolar nature, has high electron‐donating two tert ‐butyl groups, whereas HLSO 3 Na, with polar nature, has high electron‐withdrawing sodium sulfonate group.…”
Section: Resultsmentioning
confidence: 99%
“…d transition), as reported for other Fe-chelates elsewhere. [23,24] The high observed shift of the d ! d transition band between Fe (LDBu) 2 and Fe (LSO 3 Na) 2 , despite the same molecular core, could be due to the difference in the polarity and the electron-donating or electronwithdrawing power of the substituted groups in the both coordinated ligands.…”
Section: Ultra Violet and Visible Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…26 Generally, metals and alkalis co-catalyse alcohol oxidation under mild reaction conditions. 27 Kantam and co-workers 28 illustrated that the use of base was pertinent even in the presence of an alkali over Pd catalyst. On the contrary, R. Davis et al 29 has reported a much lower conversion for the gold catalysed alcohol to aldehyde oxidation without any alkali.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials with different nanostructures have been extensively employed for environmental remediation, liquid phase catalysis, supercapacitors, and electrocatalysis . Among these various applications, carbon-based supercapacitors are highly promising because of their great capability, fast charge/discharge processes, long-period stability, and low-cost.…”
Section: Introductionmentioning
confidence: 99%